FACTORS AFFECTING CLOTHING PURCHACE - İlleez, Alime Aslı; Yücel, Önder (International Journal of Research -GRANTHAALAYAH, 2023)
This study was conducted to determine the factors affecting consumers' choice during clothing purchace. Questionnaire method was used as the data collection technique in the research and data were obtained from 826 people living in Izmir province. The questionnaire consists of 8 sections. These are demographic information (age and gender), shopping frequency, the meaning of the brand, reasons for purchasing clothes, factors affecting clothing preference, the importance of the brand according to the product type, preferred places for shopping and finally the impressions created by the brand were tried to be determined. Evaluations and comments were made in the light of the data obtained.